PERAN GURU DALAM MENGATASI DISTRAKSI DI ERA DIGITAL INTERNET OF THINGS (IOT) GUNA MENINGKATKAN PRODUKTIVITAS SISWA - Faykal Faykal; Andi Tabrani Rasyid; Muhammad Yanis (TEACHING : Jurnal Inovasi Keguruan dan Ilmu Pendidikan, 2026)
The rapid development of Internet of Things technology presents new challenges in the form of digital distractions in schools, especially for 11th-grade TKJ 3 students at SMKN 1 Bone. The main research problem focuses on identifying the types of device distractions and analyzing teachers' strategic steps in optimizing student learning productivity. This study applies a descriptive qualitative methodology through participatory observation, in-depth interviews, and the comprehensive collection of official school documents. The data analysis stages are carried out systematically through reduction, categorization, and verification of field findings. The research results reveal that the misuse of smartphones for social media activities and online games is a major obstacle that causes a decline in student academic performance and delays in completing their practical assignments. To address this, educators play an active role in implementing a persuasive approach through learning contracts that contain strict rules regarding the use of electronic devices in the classroom. In addition, teachers act as proactive innovators by designing artificial intelligence-based instructional media to effectively redirect students' attention back to the learning material. The main conclusion emphasizes that the integration of regulatory discipline with the creative adaptation of technological innovation is a crucial instrument for educators to minimize digital distractions and boost student work productivity in the midst of a connected education ecosystem. This collaboration ensures that the learning environment remains conducive to the development of students' vocational competencies to face the dynamics of global industrial competition. ABSTRAK Pesatnya perkembangan teknologi Internet of Things menghadirkan tantangan baru berupa gangguan digital di sekolah, khususnya bagi siswa kelas XI TKJ 3 SMKN 1 Bone. Masalah utama penelitian berfokus pada identifikasi jenis distraksi gawai serta analisis langkah strategis guru dalam mengoptimalkan produktivitas belajar siswa. Studi ini menerapkan metodologi kualitatif deskriptif melalui observasi partisipatif, wawancara mendalam, serta pengumpulan dokumen resmi sekolah secara menyeluruh. Tahapan analisis data dilakukan sistematis lewat reduksi, kategorisasi, hingga verifikasi temuan lapangan. Hasil riset mengungkap bahwa penyalahgunaan ponsel pintar untuk aktivitas media sosial dan permainan daring menjadi penghambat utama yang menyebabkan penurunan performa akademik siswa serta keterlambatan penyelesaian tugas praktik mereka. Guna mengatasi hal tersebut, pendidik berperan aktif menerapkan pendekatan persuasif melalui kesepakatan kontrak belajar yang memuat aturan tegas mengenai pemakaian perangkat elektronik di kelas. Selain itu, guru bertindak selaku inovator proaktif dengan merancang media instruksional berbasis kecerdasan buatan demi mengalihkan atensi siswa kembali pada materi ajar secara efektif. Simpulan utama menegaskan bahwa integrasi kedisiplinan aturan dengan adaptasi inovasi teknologi secara kreatif merupakan instrumen krusial bagi pendidik untuk meminimalisir distraksi digital sekaligus mendongkrak produktivitas kerja siswa di tengah ekosistem pendidikan terkoneksi. Kolaborasi tersebut memastikan lingkungan belajar tetap kondusif bagi pengembangan kompetensi vokasi siswa demi menghadapi dinamika persaingan industri global.